Museum sebagai Media Edukasi Budaya: Literature Review pada Museum Prabu Siliwangi - Aghnia Syifa Kamilah; Ute Lies Khadijah; Yunus Winoto (Journal of Innovative and Creativity (Joecy), 2026)
Museums have an important role in safeguarding cultural heritage while making cultural knowledge accessible to the public. Their contribution is not limited to caring for collections, but also includes using collections as learning resources and media for introducing cultural values. This article reviews the role of museums in cultural preservation and education based on previous studies. A qualitative literature review was conducted following Snyder’s stages, covering review planning, literature searching and selection, evaluation, and synthesis. Literature was identified through Google Scholar using the keywords “museum,” “cultural education,” and “cultural preservation,” with publications from 2016–2026 considered. The review indicates that museums support cultural preservation through collection care, management, documentation, and digitization. They also provide educational experiences through exhibitions, learning programs, workshops, and digital technologies. Nevertheless, limitations in human resources, funding, facilities, and technological capacity remain challenges. Sustainable collection management and innovation in information delivery are therefore needed to strengthen museums’ educational and preservation functions.